Penerapan model pembelajaran inquiry based learning melalui modul ajar kurikulum merdeka belajar Siswa Sekolah Dasar - Emas Marlina (IKIP Siliwangi, 2023)
This research is motivated by the need to use appropriate learning models in implementing the independent learning curriculum. The purpose of this study was to examine Inquiry Based Learning through the independent learning curriculum module for elementary school students. The research was carried out from January to June 2022. The research subjects were Grade IV elementary school students. This research method is literature study and observation. The results of the research obtained were data on even semester final exam scores for the 2021-2022 academic year for the Mathematics abilities of fourth-grade students. The average value was 89.4, so it can be concluded that Inquiry Based Learning learning is suitable for meeting the needs of the independent learning curriculum.